Integrated Medical Emergency System work’s results. Cienfuegos, from September 2021 to September 2022 - Lázaro Armando Águila Trujillo; Mayelín Alomá Nohaya; Mileidys Roldós Guzmán; Nelson Fernández Quintana; Zenaida Rodríguez Bernal (Medisur)
Foundation: the medical emergencies integrated system has the purpose of improving the care quality for patients receiving emergency medical services. Objective: to describe the Integrated System of Medical Emergencies’ work results. Methods: descriptive, cross-sectional study, carried out between September 2021 and September 2022 in the Cienfuegos province, about the emergency system operation. The analyzed variables were: conditions and most frequent causes of transfer through the system; days and hours in which the services are requested. Results: acute respiratory diseases were the ones that most caused transfers. Among the chronic non-communicable diseases, acute myocardial infarction, acute coronary syndrome and cerebrovascular disease were the diseases, in ascending order, that most caused requests for medical transfers; Tuesday the day with the most requests. Conclusions: respiratory diseases cause a high number of requests for transfer to medical emergencies, followed by chronic non-communicable diseases.